2023
DOI: 10.3389/fcell.2023.1105565
|View full text |Cite
|
Sign up to set email alerts
|

Acquired disorders of mitochondrial metabolism and dynamics in pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is an orphan disease of the cardiopulmonary unit that reflects an obstructive pulmonary vasculopathy and presents with hypertrophy, inflammation, fibrosis, and ultimately failure of the right ventricle (RVF). Despite treatment using pulmonary hypertension (PH)-targeted therapies, persistent functional impairment reduces the quality of life for people with PAH and death from RVF occurs in approximately 40% of patients within 5 years of diagnosis. PH-targeted therapeutics ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 246 publications
(358 reference statements)
0
3
0
Order By: Relevance
“…According to numerous published papers, mitochondrial dysfunction is a therapeutic target of increasing interest in PAH [3]. The mitochondrion is the energy powerhouse of all eukaryotic cells through oxidative phosphorylation (OXPHOS).…”
Section: Introductionmentioning
confidence: 99%
“…According to numerous published papers, mitochondrial dysfunction is a therapeutic target of increasing interest in PAH [3]. The mitochondrion is the energy powerhouse of all eukaryotic cells through oxidative phosphorylation (OXPHOS).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that hypoxia can reduce the degradation of HIF-1α, a protein that plays a crucial role in gene regulation. HIF-1α is responsible for promoting the expression of various genes, including VEGF and eNOS, which are essential for cell proliferation [64][65][66]. Additionally, SRC is necessary for the expression of HIF-1α in vascular smooth muscle cells (VSMCs) [67].…”
Section: Discussionmentioning
confidence: 99%
“…The bidirectional relationship between epigenetics and metabolomics represents a significant underlying mechanism mediating the pathophysiological modulation of pulmonary vascular remodeling in PAH and warrants further investigation. These alterations underscore the critical role of metabolic adaptations in promoting fibroblast proliferation, apoptosis resistance, and inflammatory activation [ 148 , 149 ].…”
Section: Mechanisms Underlying Fibroblast Abnormalities In Phmentioning
confidence: 99%